Effect of orthodontic treatment on the periodontal tissues. Issue 1 (21st April 2017) - Antoun, Joseph S.; Mei, Li; Gibbs, Kelsi; Farella, Mauro
Abstract: Reduced periodontal support is a challenge that clinicians often face during rehabilitation of compromised dentition. The close and intricate relationship between the periodontal tissues and the processes of tooth movement suggest that adjunct orthodontic therapy may play an important role in overcoming these problems. On the other hand, excessive movement of teeth beyond the anatomic boundaries of the alveolar process is commonly believed to contribute to further destruction of the periodontal tissues. This review evaluates the clinical effects of various orthodontic tooth movements on the surrounding periodontal soft tissues and alveolar bone. Another objective was to identify possible patient and treatment‐related factors that may influence the response of periodontal tissue to specific orthodontic treatments. Particular emphasis is placed on specific tooth movements, such as extrusion, intrusion, space closure and arch expansion. Limitations of current research are also highlighted and discussed.